Chinese immigrants in Vancouver: quo vadis? - Shibao Guo; Don J. DeVoretz (Institute for the Study of Labor (IZA), 2006)
This paper reports findings from a Vancouver study which examines the settlement and adaptation experience of Chinese immigrants in Vancouver. The study reveals that non-economic reasons, such as the environment, education and citizenship, constituted the primary motivations for Chinese immigrants to move to Canada. Employment and language facilities were the most frequently cited barriers inhibiting their integration into the Vancouver social and economic spheres. Their poor economic performances coupled with the devaluation of both their acquired Chinese education qualifications and labour market experience have hindered integration and increased dissatisfaction with their lives in Canada. Given the logic of our posited triangular migration model we argue that this dissatisfaction will encourage Chinese emigration from Vancouver.
urn:nbn:de:101:1-20090825206
Keywords: 330